EAST JAVA HALAL TOURISM OUTLOOK: POTENTIAL ANALYSIS AND STRATEGY FOR EAST JAVA HALAL TOURISM DEVELOPMENT - Muhammad Mufli (East Java Economic Journal, 2018)
East Java is included in the strategic area of national halal tourism development by the Ministry of Tourism. This was supported by the existence of religious tourism objects, natural and artificial tourism attractions, organizing annual cultural events, and adequate infrastructure. The purpose of this research is to review the potential and formulate strategies for the development of halal tourism in East Java. This research uses secondary data with qualitative method and SWOT analysis technique. Internal analysis shows the strengths and weaknesses factor as well as external analysis shows the opportunity and challenge factors of weakness in the development of halal tourism in East Java. Strength factors include diversity of tourist destinations, infrastructure to support the mobility of tourists, and level of tourist visits. Weakneses factors include promotion and branding, skilled human resources, as well as supporting facilities for halal tourism. Opportunity factors include government policy support, existence of supporting institutions and international reputation of halal tourism Indonesia. Threat factors include economic stability, security stability and competition for the halal tourism industry. Based on the analysis of internal and external factors, the formulation of the development strategy of halal tourism in East Java among others : a) S-O strategy: encouraging domestic and foreign investment in the development of halal tourism in East Java; b) W-O strategy: development of East Java halal tourism information center platform; c) S-T strategy: create a brand identity for East Java halal tourism titled “Khazanah Jawa Timur”; d) W-T strategy: establishment of special economic zone for east java halal tourism.